UiTM Digital Library - UiTM, Perpustakaan Tun Abdul Razak (Perpustakaan Tun Abdul Razak, 2020)
Perpustakaan Tun Abdul Razak (PTAR) UiTM is committed to realize the aspirations of Universiti Teknologi MARA (UiTM) to continuously achieve excellence and uplift UiTM to the global level. Thus, improving the quality of the information delivery system has become the focus of PTAR in fulfilling the needs and expectations of our customers. PTAR has gone through four (4) phases of transformation before becoming a Digital Library. To ensure the library continues to be relevant and competitive, the library improves its service to its customers through service, collections and latest processes that conforms to the needs of teaching, learning and research in UiTM.